Perkembangan Kurikulum di Indonesia dalam Perspektif Sejarah - Dini Febriyenti; Nabila Putri; Asmendri Asmendri; Milya Sari (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2023)
This study aims to explain the history of curriculum development in Indonesia, several times there has been a change of curriculum which has certainly had an impact on the education process in Indonesia where we know that the curriculum is an important element in the education process in Indonesia. This study uses a qualitative method with data collection techniques through library research which involves collecting information and data from various sources in the library such as reference books, relevant previous research results, articles, related notes and including journals related to the topic to be resolved. The curriculum in Indonesia after Indonesian independence in 1945 underwent 9 changes including 1947, 1952, 1964, 1968, 1975, 1984, 1994, 2004, 2006 and 2013. Curriculum development is based on several factors, namely first. The challenges of the future are globalization, environmental problems and technological advances, convergence of science and technology and business, industrial revival. Creative industry and culture of global economic change, quality. Second, future skills are communication skills, clear and critical thinking and critical, creative and critical thinking skills and skills.